Analysis of cellular and cell free mitochondrial DNA content and reactive oxygen species levels in maternal blood during normal pregnancy: a pilot study - Anubhav Srivastava; Pransu Srivastava; Shashank Mathur; Suman Mishra; Sabiya Abbas; Amrit Gupta; Prabhaker Mishra; Meenakshi Tiwari; Lokendra Kumar Sharma (BMC, 2022)
Abstract Background Alterations in mitochondrial signatures such as mitochondrial DNA (mtDNA) content in maternal blood have been linked to pregnancy-related complications. However, changes in maternal mtDNA content, their distribution and associated signaling during normal pregnancies are not clear; which could suggest their physiological role in maternal adaptation to pregnancy related changes and a reference threshold. The aim of this study: to assess the distribution of mtDNA in peripheral blood and their association with circulatory ROS levels across different trimesters of healthy pregnancy. Methods In this pilot cross sectional study, blood samples of normal pregnant women from each trimester (total = 60) and age-matched non-pregnant (NP) women as control group (n = 20) were analyzed for a) the relative distribution of mtDNA content in cellular and cell free (plasma) fractions using relative quantitative polymerase chain reaction (qPCR) and b) the levels of circulating reactive oxygen species (ROS) by measurement of plasma H2O2. The results were compared between pregnant and NP groups and within trimesters for significant differences, and were also analyzed for their correlation between groups using statistical methods. Results While, we observed a significant decline in cellular mtDNA; plasma mtDNA was significant increased across all trimesters compared to NP. However, from comparisons within trimesters; only cellular mtDNA content in 3rd trimester was significantly reduced compared to 1st trimester, and plasma mtDNA did not differ significantly among different trimesters. A significantly higher level of plasma H2O2 was also observed during 3rd trimester compared to NP and to 1st trimester. Correlation analysis showed that, while cellular mtDNA content was negatively correlated to plasma mtDNA and to plasma H2O2 levels; plasma mtDNA was positively correlated with plasma H2O2 content. Conclusions This study suggested that normal pregnancy is associated with an opposing trend of reduced cellular mtDNA with increased circulatory mtDNA and H2O2 levels, which may contribute to maternal adaptation, required during different stages of pregnancy. Estimation of mtDNA distribution and ROS level in maternal blood could show mitochondrial functionality during normal pregnancy, and could be exploited to identify their prognostic/ diagnostic potential in pregnancy complications.